TMEM199-Congenital Disorder of Glycosylation With Novel Phenotype and Genotype in a Chinese Boy - Fang, Yuan; Abuduxikuer, Kuerbanjiang; Wang, Yi-Zhen; Li, Shao-Mei; Chen, Lian; Wang, Jian-She (Frontiers in Genetics, 2022)
Background: TMEM199-congenital disorder of glycosylation (TMEM199-CDG) is a rare autosomal recessive inherited disease characterized by chronically elevated serum transaminase, decreased serum ceruloplasmin, steatosis and/or fibrosis, TMEM199 mutation, reduced level of TMEM199 protein, and abnormal protein glycosylation. Methods: The information of a Chinese patient with TMEM199-CDG in the Children’s Hospital of Fudan University was reviewed. The patient’s clinical, pathological, and molecular features were obtained by clinical data study, liver biopsy, immunohistochemistry, and molecular genetic analysis. Results: A 4-year-old Chinese boy presented with hypertransaminasemia, hypercholesterolemia, elevated alkaline phosphatase, decreased serum ceruloplasmin and serum copper level, and coagulopathy since birth. To the best of our knowledge, novel findings included strabismus, cirrhosis by liver biopsy, reduced expression of TMEM199 by immunohistochemistry, and a frameshift variant of c.128delA/p.Lys43Argfs*25 in the TMEM199 gene. Conclusion: This case added to the phenotypic and genotypic spectrum of TMEM199-CDG.